Reforms in Political Parties Through the Balancing of Funding Sources - Delia Wildianti; Adelline Syahda (Bappenas Working Papers, 2019)
This research was conducted through qualitative methods with literature study and in-depth interviews data collecting techniques to provide an explanation on how the ideal political party funding system will influence the political party’s recruitment system to encourage the realization of a substantive democracy. The result of the research shows that Indonesia needs a reformation in the political party funding source system by increasing the funding from the state and by involving their constituents. The aim is to break dependence from political party elites and to strengthen the relationship between the constituents and their parties. It can be concluded that political party reform through the role of the state and constituents should also be followed by periodic reports from parties to encourage transparency and financial accountability. Furthermore, it needs to be accompanied by administrative sanctions in the form of reduction or revocation of financial assistance by the state on the event that the party fails to fulfill its obligations.